2019
DOI: 10.29289/2594539420190000443
|View full text |Cite
|
Sign up to set email alerts
|

Imaging findings of absorbable Vicryl mesh implanted after lumpectomy

Abstract: A implantação da tela de Vicryl após quadrantectomia, proposta pela primeira vez em 2003, é uma técnica simples, sendo menos dispendiosa do que outros biomateriais implantáveis. Entretanto, o acompanhamento pós-operatório pode ser difícil, uma vez que a tela implantada compromete a avaliação do parênquima mamário adjacente, tanto na mamografia quanto na ultrassonografia. A ressonância magnética pode ser utilizada se houver achados duvidosos no exame físico, na mamografia ou na ultrassonografia. No entanto, exi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 4 publications
0
2
0
Order By: Relevance
“…However, although visualization of the breast parenchyma may be impaired with ultrasound and mammography, magnetic resonance imaging can be used as a problem-solving tool. 20 Ultimately, a foreign body in the breast remains a risk factor for infection, 21 and only one case report exists of a chronic abscess in a patient who underwent mastopexy with a polypropylene mesh. 22 Eventually, fat grafting for further volume enhancement and projection can be considered as an adjunct tool in some patients, mainly to achieve upper pole fullness.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, although visualization of the breast parenchyma may be impaired with ultrasound and mammography, magnetic resonance imaging can be used as a problem-solving tool. 20 Ultimately, a foreign body in the breast remains a risk factor for infection, 21 and only one case report exists of a chronic abscess in a patient who underwent mastopexy with a polypropylene mesh. 22 Eventually, fat grafting for further volume enhancement and projection can be considered as an adjunct tool in some patients, mainly to achieve upper pole fullness.…”
Section: Discussionmentioning
confidence: 99%
“…Our series did not incur any breast biopsies or interference with breast imaging, and no series of mastopexy with mesh has established such concerns. Nevertheless, Bitencourt et al indicate that breast imaging for patients with Vicryl mesh is reported to exhibit a “typical foreign body granulomatous reaction,” 20 and that “breast radiologists and surgeons should be aware of these imaging aspects to avoid misdiagnosis and unnecessary additional exams.” 20 As for the ProGrip mesh, none of our patients who underwent volume distribution mastopexy with ProGrip mesh had reported any problem with visualization of their breast imaging (Fig. 2, below ).…”
Section: Discussionmentioning
confidence: 99%